A novel mutation in GPD1‑L associated with early repolarization syndrome via modulation of cardiomyocyte fast sodium currents - Fan, Jun; Ji, Cheng‑Cheng; Cheng, Yun‑Jiu; Yao, Hao; Chen, Xu‑Miao; Zheng, Zi‑Heng; Wu, Su‑Hua (International journal of molecular medicine, 2020)
Early repolarization syndrome (ERS) is associated with genetic mutations, but the role of the glycerol‑3‑phosphate dehydrogenase 1‑like (GPD1‑L) mutation remains unclear. The aim of the present study was to investigate the role and potential underlying mechanism of GPD1‑L mutation P112L in the pathogenesis of ERS. Whole‑genome sequencing was performed on samples from a family with ERS, and the gene sequencing results were analyzed using bioinformatics. 293 cells were transfected with wild‑type (WT) or mutant‑type (MT) GPD1‑L and SCN5A plasmids. Successful transfection of GPD1‑L in 293 cells was verified by western blotting. Whole‑cell patch‑clamp recording, confocal microscopic observation and western blotting were used to uncover the potential mechanism of GPD1‑L P112L in ERS. The results of western blotting indicated that the expression of the GPD1‑L protein was lower in the MT group compared with that in the WT group, but the mock group did not express the GPD1‑L protein. The whole‑cell patch‑clamp recording results indicated that the activation current density of INa (at ‑30 mV) was ~60% lower in the MT group compared with the WT group (P<0.01). The mutation caused the inactivation voltage to move in a negative direction by ~3 mV compared with that of the WT group. However, there were no significant between‑group differences in the steady activation, steady inactivation, and steady recovery of INa. Confocal microscopy demonstrated that MT GPD1‑L was less expressed near the cell membrane and more expressed in the cytoplasm compared with WT GPD1‑L. Both WT and MT GPD1‑L were highly expressed in the cytoplasm and in small amounts in the nucleus. In conclusion, the GPD1‑L P112L mutation decreased INa activation and GPD1‑L cell expression, including in the region near the cell membrane. These results suggest that GPD1‑L P112L may be a pathogenic genetic mutation associated with ERS.